Atlantic-Camtraps: a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Lima, Fernando (2017)
Fil: Lima, Fernando. Universidade Estadual Paulista. Instituto de Biociências. Departamento de Ecología; Brasil.